Wybrane koszty uczestnictwa w unii walutowej - Biegun, Krzysztof (Selected Costs of Participation in a Monetary Union, 2005)
Participation in a monetary union brings not only benefits, but also significant costs. These costs should be estimated before joining the union. The OCA criteria made the important tool that allows to reconnaissance them. But the degree of symmetry of contemporaneous shocks is only one aspect of the costs associated with monetary union membership. There might be other costs of EMU accession of at least the same importance as dissimilarity of shocks, for example, the incompatibility of the current Maastricht criteria with the catching-up objective.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 134-144